Formation of social entrepreneurial intention: A qualitative grounded approach at the base of the pyramid - Frederik Claeyé; Yosra Boughattas; Erno T. Tornikoski (Administrative Sciences, 2022)
While there have been some attempts at investigating and theorizing social entrepreneurial action at the base of the economic pyramid, our understanding of the processes contributing to the formation of social entrepreneurial intention in contexts of extreme poverty remain limited. In this study, we aim to address this gap by providing a better understanding of the formation of social entrepreneurial intentions of youths at the base of the economic pyramid. Drawing on a qualitative grounded approach, we highlight the role of self-confidence, perceived self-efficacy and social ascension beliefs as important drivers in understanding the formation of social entrepreneurial intention of youths at the base of the pyramid. At a practical level, our study suggests that besides developing entrepreneurship-specific knowledge, support mechanisms should also pay attention to the development of different self-related beliefs of youths to enable the formation of social entrepreneurial intention at the base of the pyramid.
Keywords: 350; social entrepreneurship; base of the pyramid (BoP); entrepreneurial intentions; self-beliefs